2022
DOI: 10.1016/j.bioactmat.2021.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive extracellular matrix scaffolds engineered with proangiogenic proteoglycan mimetics and loaded with endothelial progenitor cells promote neovascularization and diabetic wound healing

Abstract: Diabetic ischemic wound treatment remains a critical clinical challenge. Neovascularization plays a significant role in wound healing during all stages of the tissue repair process. Strategies that enhance angiogenesis and neovascularization and improve ischemic pathology may promote the healing of poor wounds, particularly diabetic wounds in highly ischemic conditions. We previously identified a cyclic peptide LXW7 that specifically binds to integrin αvβ3 on endothelial progenitor cells (EPCs) and endothelial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Neovascularization is responsible for the transport of inflammatory cells, nutrients, chemokines, and cytokines, as well as the removal of waste, which plays a pivotal role in fast wound healing. 29 Here, both SIS-PAAm and SIS-PNIPAm hydrogel promoted the migration of HUVECs (Fig. 2C) with a significantly higher relative migration area (Fig.…”
mentioning
confidence: 68%
“…Neovascularization is responsible for the transport of inflammatory cells, nutrients, chemokines, and cytokines, as well as the removal of waste, which plays a pivotal role in fast wound healing. 29 Here, both SIS-PAAm and SIS-PNIPAm hydrogel promoted the migration of HUVECs (Fig. 2C) with a significantly higher relative migration area (Fig.…”
mentioning
confidence: 68%
“…We further demonstrated that LXW7 can support both endogenous and exogenous EC binding and enhanced EC proliferation and functionality (Hao et al, 2023; Hao, Fan, et al, 2020; He et al, 2022). In one study, we engineered biomaterial scaffolds with LXW7 and loaded the scaffold with exogenous EPCs and showed that this approach significantly promotes neovascularization and diabetic wound healing in a Zucker Diabetic Fatty (ZDF) rat ischemic skin flap model (He et al, 2022). In another recent study, we applied LXW7 to functionalize the biomaterial scaffold and showed that this technology effectively regulates endogenous EC and EPC adhesion and promotes vascularized bone regeneration for both adult and fetal birth defects (Hao et al, 2023).…”
Section: Bioactive Peptidesmentioning
confidence: 83%
“…Collagen proteins, including type Ⅰ and Ⅲ, are the primary constituents in dermal extracellular matrix [ 53 ]. Previous studies revealed that early abundant deposition of collagen III would accelerate wound healing and result in scarless skin [ 53 , 54 ]. Masson staining was done to visualize the total collagen proteins [ 6 ].…”
Section: Resultsmentioning
confidence: 99%